Revised timing of cenozoic atlantic incursions and changing hinterland sediment sources during southern patagonian orogenesis - Fosdick, Julie C. (2020)
New detrital zircon U-Pb geochronology data from the Cenozoic Magallanes-Austral Basin in Argentina and Chile ~51° S establish a revised chronostratigraphy of Paleocene-Miocene foreland synorogenic strata and document the rise and subsequent isolation of hinterland sources in the Patagonian Andes from the continental margin. The upsection loss of zircons derived from the hinterland Paleozoic and Late Jurassic sources between ca. 60 and 44Ma documents a major shift in sediment routing due to Paleogene orogenesis in the greater Patagonian-Fuegian Andes. Changes in the proportion of grains from hinterland thrust sheets, comprised of Jurassic volcanics and Paleozoic metasedimentary rocks, provide a trackable signal of long-term shifts in orogenic drainage divide and topographic isolation due to widening of the retroarc fold-thrust belt. The youngest detrital zircon U-Pb ages confirm timing of Maastrichtian-Eocene strata but require substantial age revisions for part of the overlying Cenozoic basinfill during the late Eocene and Oligocene. The upper Río Turbio Formation, previously mapped as middle to late Eocene in the published literature, records a newly recognized latest Eocene-Oligocene (37-27Ma) marine incursion along the basin margin. We suggest that these deposits could be genetically linked to the distally placed units along the Atlantic coast, including the El Huemul Formation and the younger San Julián Formation, via an eastward deepening within the foreland basin system that culminated in a basin-wide Oligocene marine incursion in the Southern Andes. The overlying Río Guillermo Formation records onset of tectonically generated coarse-grained detritus ca. 24.3Ma and a transition to the first fully nonmarine conditions on the proximal Patagonian platform since Late Cretaceous time, perhaps signaling a Cordilleran-scale upper plate response to increased plate convergence and tectonic plate reorganization.